Neocybernetics and narrative - Clarke, Bruce, 1950- (Posthumanities ;, 2014)
This study rethinks narrative and media through systems theory. Reconceiving interrelations among subjects, media, significations, and the social, it demonstrates second-order systems theory's potential to provide fresh insights into the familiar topics of media studies and narrative theory. The book offers a synthesis of the neocybernetic theories of cognition formulated by biologists Humberto Maturana and Francisco Varela, incubated by cyberneticist Heinz von Foerster, and cultivated in Niklas Luhmann's social systems theory.